All-solid battery

The all-solid-state battery design optimizes the use of fibrous carbon nanotubes as conductive additives within specific parameters to enhance conductivity and yield, addressing capacity and responsiveness issues in existing batteries.

JP2025000289APending Publication Date: 2025-01-07TAIYO YUDEN KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023100065
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing all-solid-state batteries face challenges in achieving high capacity and responsiveness while maintaining good battery operation and yield, particularly due to the use of carbon materials as conductive additives which can decrease yield and battery capacity.

Method used

The battery design includes a solid electrolyte layer with specific parameters for conductive additives, such as a diameter range, area ratio, and thickness, using fibrous carbon materials like carbon nanotubes to enhance conductivity without compromising battery capacity.

Benefits of technology

The design achieves improved battery operation and yield by optimizing the ratio of conductive additives that do not contribute to capacity, ensuring sufficient conductivity and reducing the risk of short circuits and cavities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025000289000001_ABST
    Figure 2025000289000001_ABST
Patent Text Reader

Abstract

To provide an all-solid battery capable of achieving both favorable battery operation and improved yield while suppressing the ratio of a conductive auxiliary agent at a low value, the conductive auxiliary agent not contributing to the capacity.SOLUTION: An all-solid battery includes a solid electrolyte layer, and electrode layers that are provided on both main faces of the solid electrolyte layer and include an electrode active material and a carbon-based conductive auxiliary agent. In a cross section of each electrode layer, an average diameter of the conductive auxiliary agent is 5 nm or more and less than 150 nm, and a GD ratio of the conductive auxiliary agent is 0.5 or more and 20 or less. In the cross section of each electrode layer, an area ratio occupied by the conductive auxiliary agent is more than 0.5% and 10% or less, and a thickness of the solid electrolyte layer is 5 μm or more and 20 μm or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an all-solid-state battery. [Background technology]

[0002] All-solid-state batteries using oxide-based solid electrolytes are expected to be a technology that can provide safe secondary batteries that do not suffer from concerns about fire and toxic gas emissions, which are associated with organic electrolytes and sulfide-based solid electrolytes (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2021 / 095757 [Patent Document 2] International Publication No. 2014 / 042083 Summary of the Invention [Problem to be solved by the invention]

[0004] The structure in which thin layers of solid electrolyte and internal electrodes are alternately laminated is expected to achieve both high battery capacity and high responsiveness. Chip-type small all-solid-state batteries are required to have a higher capacity within a limited component volume.

[0005] It has been considered to use a carbon material as a conductive additive in the electrode layer. However, since the conductive additive does not contribute to the battery capacity, if the amount of the conductive additive is increased to improve the conductivity, there is a risk that good battery operation cannot be obtained. In addition, the use of a carbon material may reduce the yield.

[0006] The present invention has been made in consideration of the above problems, and has an object to provide an all-solid-state battery that can achieve good battery operation and improved yield while keeping the ratio of conductive additives that do not contribute to capacity low. [Means for solving the problem]

[0007] The all-solid-state battery according to the present invention comprises a solid electrolyte layer, and electrode layers provided on both main surfaces of the solid electrolyte layer and containing an electrode active material and a carbon-based conductive additive, wherein in a cross section of each of the electrode layers, the average diameter of the conductive additive is 5 nm or more and less than 150 nm, the GD ratio of the conductive additive is 0.5 or more and 20 or less, the area ratio of the conductive additive is more than 0.5% and 10% or less in a cross section of the electrode layer, and the thickness of the solid electrolyte layer is 5 μm or more and 20 μm or less.

[0008] In the all-solid-state battery, the conductive assistant may be a fibrous conductive material.

[0009] In the all-solid-state battery, the conductive assistant may be a carbon nanotube.

[0010] In the all-solid-state battery, the conductive assistant may be a multi-walled carbon nanotube.

[0011] In the all-solid-state battery, the solid electrolyte layer may be an oxide.

[0012] In the all-solid-state battery, the solid electrolyte layer may be a phosphate-based oxide.

[0013] In the all-solid-state battery, the solid electrolyte layer and the electrode layer may be sintered bodies. Effect of the Invention

[0014] According to the present invention, it is possible to provide an all-solid-state battery that can realize good battery operation and improved yield while keeping the ratio of conductive additive that does not contribute to capacity low. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a basic structure of an all-solid-state battery. [Diagram 2]FIG. [Diagram 3] FIG. 2 is a partial cross-sectional perspective view of a stacked-type all-solid-state battery in which a plurality of battery units are stacked. [Figure 4] FIG. 2 is a partial cross-sectional perspective view of a stacked-type all-solid-state battery in which a plurality of battery units are stacked. [Diagram 5] 1A and 1B are perspective views illustrating an example of a conductive additive, and FIG. 1C is a cross-sectional view illustrating a laminated positive electrode layer. [Figure 6] FIG. 1 is a diagram illustrating a flow of a method for producing an all-solid-state battery. [Figure 7] 1(a) to 1(c) are diagrams illustrating a lamination process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, an embodiment will be described with reference to the drawings.

[0017] (Embodiment) Fig. 1 is a schematic cross-sectional view showing a basic structure of an all-solid-state battery 100 according to an embodiment. As illustrated in Fig. 1, the all-solid-state battery 100 has a structure in which a solid electrolyte layer 30 is sandwiched between a positive electrode layer 10 and a negative electrode layer 20. For example, the positive electrode layer 10 is formed on a first main surface of the solid electrolyte layer 30, and the negative electrode layer 20 is formed on a second main surface of the solid electrolyte layer 30. The positive electrode layer 10, the negative electrode layer 20, and the solid electrolyte layer 30 are sintered bodies.

[0018] The solid electrolyte layer 30 is mainly composed of a solid electrolyte having ion conductivity. The solid electrolyte of the solid electrolyte layer 30 is, for example, an oxide-based solid electrolyte having lithium ion conductivity. The solid electrolyte is, for example, a phosphate-based solid electrolyte having a NASICON structure. The phosphate-based solid electrolyte having a NASICON structure has a high electrical conductivity and is stable in the air. The phosphate-based solid electrolyte is, for example, a phosphate containing lithium. The phosphate is not particularly limited, but examples thereof include a composite lithium phosphate salt with Ti (for example, LiTi2(PO4)3). Alternatively, Ti can be partially or completely replaced with a tetravalent transition metal such as Ge, Sn, Hf, or Zr. In order to increase the Li content, it may be partially replaced with a trivalent transition metal such as Al, Ga, In, Y, or La. More specifically, for example, Li 1+x Al x Ge 2-x (PO4)3 and Li 1+x Al x Zr 2-x (PO4)3, Li 1+x Al x Ti 2-x (PO4)3. For example, Li-Al-Ge-PO4-based material to which the same transition metal as that contained in the phosphate having an olivine crystal structure contained in the positive electrode layer 10 and the negative electrode layer 20 is added in advance is preferable. For example, when the positive electrode layer 10 and the negative electrode layer 20 contain a phosphate containing Co and Li, it is preferable that the solid electrolyte layer 30 contains a Li-Al-Ge-PO4-based material to which Co is added in advance. In this case, the effect of suppressing the elution of the transition metal contained in the electrode active material into the electrolyte can be obtained. When the positive electrode layer 10 and the negative electrode layer 20 contain a phosphate containing a transition element other than Co and Li, it is preferable that the solid electrolyte layer 30 contains a Li-Al-Ge-PO4-based material to which the transition metal is added in advance.

[0019] As illustrated in FIG. 2, the positive electrode layer 10 has a structure in which an electrode active material 11, a solid electrolyte 12, a conductive assistant 13, and the like are dispersed. The negative electrode layer 20 has a structure in which an electrode active material 21, a solid electrolyte 22, a conductive assistant 23, and the like are dispersed. The positive electrode layer 10 includes the electrode active material 11, and the negative electrode layer 20 includes the electrode active material 21, so that the all-solid-state battery 100 can be used as a secondary battery. The positive electrode layer 10 includes the solid electrolyte 12, and the negative electrode layer 20 includes the solid electrolyte 22, so that the positive electrode layer 10 and the negative electrode layer 20 have ion conductivity. The positive electrode layer 10 includes the conductive assistant 13, and the negative electrode layer 20 includes the conductive assistant 23, so that the positive electrode layer 10 and the negative electrode layer 20 have conductivity.

[0020] The electrode active material 11 is, for example, an electrode active material having an olivine crystal structure. The electrode active material having an olivine crystal structure may also be contained in the negative electrode layer 20. An example of such an electrode active material is a phosphate containing a transition metal and lithium. The olivine crystal structure is a crystal that natural olivine has, and can be identified by X-ray diffraction.

[0021] A typical example of an electrode active material having an olivine crystal structure is LiCoPO4 containing Co and P. Phosphates in which the transition metal Co is substituted in this chemical formula can also be used. The ratio of Li and PO4 can vary depending on the valence. It is preferable to use Co, Mn, Fe, Ni, etc. as the transition metal. LiCo2P3O 10 , Li2CoP2O7, Li6Co5(P2O7)4, etc. can also be used.

[0022] For example, when an electrode active material having an olivine crystal structure is contained only in the positive electrode layer 10, the electrode active material acts as a positive electrode active material. When an electrode active material having an olivine crystal structure is also contained in the negative electrode layer 20, although the mechanism of action is not completely clear, the effect of increasing the discharge capacity and increasing the operating potential with discharge is exhibited, which is presumed to be based on the formation of a partial solid solution state with the negative electrode active material.

[0023] When both the positive electrode layer 10 and the negative electrode layer 20 contain an electrode active material having an olivine crystal structure, the electrode active materials preferably contain transition metals that may be the same or different from each other. "May be the same or different from each other" means that the electrode active materials contained in the positive electrode layer 10 and the negative electrode layer 20 may contain the same type of transition metal, or may contain different types of transition metals. The positive electrode layer 10 and the negative electrode layer 20 may contain only one type of transition metal, or may contain two or more types of transition metals. Preferably, the positive electrode layer 10 and the negative electrode layer 20 contain the same type of transition metal. More preferably, the electrode active materials contained in both electrodes have the same chemical composition. If the positive electrode layer 10 and the negative electrode layer 20 contain the same type of transition metal or contain an electrode active material of the same composition, the similarity of the compositions of the two internal electrode layers is increased, so that even if the terminals of the all-solid-state battery 100 are attached in the opposite direction, the battery can withstand practical use without malfunction depending on the application.

[0024] The negative electrode layer 20 functions as a negative electrode layer by including the electrode active material 21. By including the negative electrode active material in only one electrode, it becomes clear that the one electrode acts as a negative electrode and the other electrode acts as a positive electrode. However, both electrodes may include a material that is known as a negative electrode active material. For the negative electrode active material of the electrode, reference can be made to conventional techniques in secondary batteries as appropriate, and examples thereof include compounds such as titanium oxide, lithium titanium composite oxide, lithium titanium composite phosphate, carbon, and lithium vanadium phosphate.

[0025] The solid electrolyte 12 and the solid electrolyte 22 are not particularly limited as long as they are oxide-based solid electrolytes having ion conductivity. The solid electrolyte 12 and the solid electrolyte 22 are, for example, oxide-based solid electrolytes having lithium ion conductivity. The solid electrolyte is, for example, a phosphate-based solid electrolyte having a NASICON structure. The phosphate-based solid electrolyte is, for example, a phosphate containing lithium. The phosphate is not particularly limited, but examples thereof include a composite lithium phosphate salt with Ti (for example, LiTi2(PO4)3). Alternatively, Ti can be partially or completely replaced with a tetravalent transition metal such as Ge, Sn, Hf, or Zr. In addition, in order to increase the Li content, it may be partially replaced with a trivalent transition metal such as Al, Ga, In, Y, or La. More specifically, for example, Li 1+x Al x Ge 2-x (PO4)3 and Li 1+x Al x Zr 2-x (PO4)3, Li 1+x Al x Ti 2-x (PO4)3, etc. The solid electrolyte 12 and the solid electrolyte 22 may be, for example, the same as the main component solid electrolyte of the solid electrolyte layer 30. Alternatively, when the electrode active material contains Co and P, the solid electrolytes 12 and 22 preferably contain Co. Although the detailed mechanism is unclear, the inclusion of Co during co-firing tends to improve the oxidation resistance stability of the solid electrolyte, which makes it easier to ensure cycle stability.

[0026] In this embodiment, a relatively soft carbon-based material is used as the conductive assistant 13, 23. A metal may be further used in addition to the carbon-based conductive assistant 13, 23. Examples of the metal of the conductive assistant include Pd, Ni, Cu, Fe, and alloys containing these.

[0027] 3 is a schematic cross-sectional view of a stacked type all-solid-state battery 100a in which a plurality of battery units are stacked. The all-solid-state battery 100a includes a stacked chip 60 having a substantially rectangular parallelepiped shape. In the stacked chip 60, a first external electrode 40a and a second external electrode 40b are provided so as to contact two side surfaces, which are two of the four surfaces other than the upper and lower surfaces at the ends in the stacking direction. The two side surfaces may be two adjacent side surfaces, or may be two side surfaces facing each other. In this embodiment, the first external electrode 40a and the second external electrode 40b are provided so as to contact two side surfaces facing each other (hereinafter referred to as two end surfaces).

[0028] In the following description, components having the same composition range, thickness range, and particle size distribution range as those of the all-solid-state battery 100 are denoted by the same reference numerals and detailed description thereof will be omitted.

[0029] In the all-solid-state battery 100a, a plurality of positive electrode layers 10 and a plurality of negative electrode layers 20 are alternately stacked with a solid electrolyte layer 30 interposed therebetween. The edges of the plurality of positive electrode layers 10 are drawn to the first end face of the stacked chip 60, but are not drawn to the second end face. The edges of the plurality of negative electrode layers 20 are drawn to the second end face of the stacked chip 60, but are not drawn to the first end face. As a result, the positive electrode layer 10 is electrically connected to the first external electrode 40a, and the negative electrode layer 20 is electrically connected to the second external electrode 40b. The solid electrolyte layer 30 extends from the first external electrode 40a to the second external electrode 40b. In this way, the all-solid-state battery 100a has a structure in which a plurality of battery units are stacked.

[0030] A cover layer 50 is laminated on the upper surface of the laminated structure of the positive electrode layer 10, the solid electrolyte layer 30, and the negative electrode layer 20 (in the example of FIG. 3, the upper surface of the uppermost positive electrode layer 10). In addition, a cover layer 50 is laminated on the lower surface of the laminated structure (in the example of FIG. 3, the lower surface of the lowermost positive electrode layer 10). The cover layer 50 is mainly composed of an inorganic material (e.g., Al2O3, ZrO2, TiO2, etc.) containing, for example, Al, Zr, Ti, etc. The cover layer 50 may contain the main component of the solid electrolyte layer 30 as a main component. The cover layer 50 is a sintered body.

[0031] The positive electrode layer 10 and the negative electrode layer 20 may each include a current collector layer. For example, as illustrated in FIG. 4, a first current collector layer 15 may be provided in the positive electrode layer 10. A second current collector layer 25 may be provided in the negative electrode layer 20. The first current collector layer 15 and the second current collector layer 25 are mainly composed of a conductive material. For example, metal, carbon, etc. may be used as the conductive material of the first current collector layer 15 and the second current collector layer 25. The current collection efficiency is improved by connecting the first current collector layer 15 to the first external electrode 40a and connecting the second current collector layer 25 to the second external electrode 40b.

[0032] As described above, the positive electrode layer 10 and the negative electrode layer 20 contain a conductive assistant from the viewpoint of electrical conductivity. However, if the electrical conductivity of the conductive assistant is low, a certain amount of the conductive assistant is required to provide good electrical conductivity to the positive electrode layer 10 and the negative electrode layer 20. However, if the content of the conductive assistant that does not contribute to the battery capacity increases, the battery capacity in the positive electrode layer 10 and the negative electrode layer 20 decreases.

[0033] Therefore, in this embodiment, a lower limit is set for the GD ratio of the conductive assistants 13 and 23. Here, the GD ratio of the conductive assistants 13 and 23 can be measured by performing Raman spectroscopy on the conductive assistants 13 and 23. Specifically, the measurement is performed under conditions of an excitation wavelength of 487.88 nm and a grating L of 600, and the GD ratio is 1300 cm -1 ~1400cm -1 and peak intensities ID in the range of 1500 cm -1 ~1600cm -1 Peak intensities IG and ID in the range of IG / ID are measured, and the ratio (IG / ID) is defined as the GD ratio. In this embodiment, the GD ratio is set to 0.5 or more. This improves the conductivity of the conductive assistants 13 and 23, and the content of the conductive assistant 13 in the positive electrode layer 10 can be reduced, and the content of the conductive assistant 23 in the negative electrode layer 20 can be reduced. In addition, when the GD ratio is 0.5 or more, the thermal stability of the conductive assistants 13 and 23 is improved, so that high conductivity can be obtained in the positive electrode layer 10 and the negative electrode layer 20 even when the all-solid-state battery 100 is formed by high-temperature firing.

[0034] On the other hand, if the GD ratio of the conductive assistants 13 and 23 is high, the deformation of the positive electrode layer 10 and the negative electrode layer 20 does not follow the deformation of the solid electrolyte layer 30 during firing, and cavities are formed in the positive electrode layer 10 and the negative electrode layer 20, which may reduce the yield of the all-solid-state battery 100 and 100a. Therefore, in this embodiment, an upper limit is set for the GD ratio of the conductive assistants 13 and 23. Specifically, the GD ratio of the conductive assistants 13 and 23 is set to 20 or less. This suppresses the formation of cavities in the positive electrode layer 10 and the negative electrode layer 20, and improves the yield of the all-solid-state battery 100.

[0035] Next, if the average diameter of the conductive assistants 13, 23 is large, there is a risk that the conductive assistants 13, 23 will break through the solid electrolyte green sheet before firing. Therefore, an upper limit is set for the average diameter of the conductive assistants 13, 23. In this embodiment, the average diameter of the conductive assistants 13 in the cross section of the positive electrode layer 10 is set to less than 150 nm, and the average diameter of the conductive assistants 23 in the cross section of the negative electrode layer 20 is set to less than 150 nm. For example, the above cross section may be a cross section including the stacking direction.

[0036] On the other hand, if the average diameter of the conductive assistants 13, 23 is small, sufficient conductivity may not be obtained for the conductive assistants 13, 23. Therefore, a lower limit is set for the average diameter of the conductive assistants 13, 23. In this embodiment, the average diameter of the conductive assistants 13 in the cross section of the positive electrode layer 10 is set to 5 nm or more, and the average diameter of the conductive assistants 23 in the cross section of the negative electrode layer 20 is set to 5 nm or more.

[0037] Next, if the content of the conductive assistant 13, 23 that does not contribute to the battery capacity is large, there is a risk that sufficient battery capacity cannot be obtained for the all-solid-state battery 100, 100a. Therefore, an upper limit is set for the content of the conductive assistant 13, 23. In this embodiment, the area ratio of the conductive assistant 13 in the cross section of the positive electrode layer 10 is set to 10% or less, and the area ratio of the conductive assistant 23 in the cross section of the negative electrode layer 20 is set to 10% or less.

[0038] On the other hand, if the amount of the conductive assistant 13, 23 is small, sufficient conductivity may not be obtained in the positive electrode layer 10 and the negative electrode layer 20. Therefore, a lower limit is set for the content of the conductive assistant 13, 23. In this embodiment, the area ratio of the conductive assistant 13 in the cross section of the positive electrode layer 10 is set to a value exceeding 0.5%, and the area ratio of the conductive assistant 23 in the cross section of the negative electrode layer 20 is set to a value exceeding 0.5%.

[0039] Next, if the solid electrolyte layer 30 is thin, the solid electrolyte green sheet before sintering may be broken by the conductive assistants 13, 23, causing a short circuit. Therefore, a lower limit is set for the thickness of the solid electrolyte layer 30. In this embodiment, the thickness of the solid electrolyte layer 30 is set to 0.5 μm or more.

[0040] On the other hand, if the solid electrolyte layer 30 is too thick, the rate characteristics of the all-solid-state batteries 100, 100a may decrease, resulting in a risk of deterioration in battery characteristics. Therefore, an upper limit is set for the thickness of the solid electrolyte layer 30. In this embodiment, the thickness of the solid electrolyte layer 30 is set to 20 μm or less.

[0041] As described above, the GD ratio of the conductive assistant 13, 23 is 0.5 or more and 20 or less, the average diameter of the conductive assistant 13 in the cross section of the positive electrode layer 10 is 5 nm or more and less than 150 nm, the average diameter of the conductive assistant 23 in the cross section of the negative electrode layer 20 is 5 nm or more and less than 150 nm, the area ratio of the conductive assistant 13 in the cross section of the positive electrode layer 10 is more than 0.5% and 10% or less, the area ratio of the conductive assistant 23 in the cross section of the negative electrode layer 20 is more than 0.5% and 10% or less, and the thickness of the solid electrolyte layer 30 is 5 μm or more and 20 μm or less, thereby achieving good battery operation and improved yield while keeping the ratio of the conductive assistant that does not contribute to capacity low.

[0042] From the viewpoint of increasing the conductivity of the conductive assistants 13 and 23, the GD ratio of the conductive assistants 13 and 23 is preferably 1.0 or more, and more preferably 2.0 or more. From the viewpoint of suppressing a decrease in the yield of the all-solid-state batteries 100 and 100a, the GD ratio of the conductive assistants 13 and 23 is preferably 16 or less, and more preferably 10 or less.

[0043] From the viewpoint of suppressing breakthrough of the solid electrolyte green sheet before firing, the average diameter of each of the conductive assistants 13, 23 is preferably 130 nm or less, and more preferably 80 nm or less. In order to provide the conductive assistants 13, 23 with sufficient conductivity, the average diameter of each of the conductive assistants 13, 23 is preferably 5 nm or more, and more preferably 8 nm or more.

[0044] In order to provide the all-solid-state batteries 100, 100a with sufficient battery capacity, the area ratio of the conductive assistant 13 in the cross section of the positive electrode layer 10 and the area ratio of the conductive assistant 23 in the cross section of the negative electrode layer 20 are preferably 10% or less, and more preferably 8% or less. In order to provide the positive electrode layer 10 and the negative electrode layer 20 with sufficient conductivity, the area ratio of the conductive assistant 13 in the cross section of the positive electrode layer 10 and the area ratio of the conductive assistant 23 in the cross section of the negative electrode layer 20 are preferably 1% or more, and more preferably 2% or more.

[0045] From the viewpoint of suppressing breakthrough of the solid electrolyte green sheet before firing, the thickness of the solid electrolyte layer 30 is preferably 6 μm or more, and more preferably 7 μm or more. From the viewpoint of suppressing deterioration of the rate characteristics of the all-solid-state battery 100, 100a, the thickness of the solid electrolyte layer 30 is preferably 19 μm or less, and more preferably 18 μm or less.

[0046] The material of the conductive assistant 13, 23 is not particularly limited as long as it is a carbon-based material, but is preferably a fibrous carbon material. In this case, the width of the conductive assistant 13, 23 is small, so that an ion conduction path between the positive electrode layer 10 and the negative electrode layer 20 can be secured compared to the case where plate-like carbon is used. It is preferable to use carbon nanotubes as the conductive assistant 13, 23. Carbon nanotubes have a hollow fiber shape and are soft, so that they can suppress breakthrough of the solid electrolyte layer 30. In particular, it is preferable to use multi-layered carbon nanotubes as the conductive assistant 13, 23.

[0047] In addition, from the viewpoint of ensuring the content of the electrode active material, the area ratio of the electrode active material 11 in the positive electrode layer 10 and the area ratio of the electrode active material 21 in the negative electrode layer 20 in the laminate cross section are preferably 30% or more, and more preferably 40% or more.

[0048] On the other hand, from the viewpoint of ensuring the solid electrolyte content, the area ratio of the electrode active material 11 in the positive electrode layer 10 and the area ratio of the electrode active material 21 in the negative electrode layer 20 are preferably 75% or less, and more preferably 70% or less.

[0049] Fig. 5(a) is a perspective view illustrating the conductive assistant 13, 23. As illustrated in Fig. 5(a), the conductive assistant 13, 23 has, for example, a fibrous shape and has a long diameter and a short diameter. The aspect ratio (long diameter:short diameter), which is the ratio of the long diameter to the short diameter, is preferably 100:1 to 3000:1, more preferably 125:1 to 1000:1, and further preferably 150:1 to 500:1.

[0050] In order to ensure a sufficient conductive distance, the overall length of the conductive assistants 13, 23 is preferably 1.5 μm or more, more preferably 2.5 μm or more, and even more preferably 5 μm or more.

[0051] The conductive assistants 13, 23 do not need to extend linearly in the positive electrode layer 10 and the negative electrode layer 20, and may be curved as shown in FIG. 5(b). When carbon nanotubes are used, the hollow portion may be a gap or may be filled with other materials. When a fibrous carbon material is used, it is preferable that the carbon material has a particle diameter of 5 nm or more in order to achieve sufficient thermal stability.

[0052] FIG. 5(c) is a diagram illustrating a cross section of the positive electrode layer 10. The cross section of the stack can be exposed by grinding the solid-state battery 100, 100a. The cross section of the stack can be observed with a scanning electron microscope (SEM) or the like. The average diameter of the conductive assistant 13 can be obtained by randomly observing 50 conductive assistants 13, measuring the shortest part, and calculating the average value. The average diameter of the conductive assistant 23 in the negative electrode layer 20 can also be measured in a similar manner. The area ratio of the conductive assistant 13 can be measured by, for example, using image analysis software (ImageJ Fiji: Schneider, CA, Rasband, WS, Elieiri, KW "NIH Image to ImageJ: 25 years of image analysis." Nature Methods 9, 671-675, 2012) to determine the ratio of the cross-sectional area of ​​the conductive assistant 13 to the total area of ​​the SEM image. The area ratio of the conductive assistant 23 in the negative electrode layer 20 can also be measured in a similar manner.

[0053] The thickness of the solid electrolyte layer 30 can be measured by observing a cross section of the stack of the all-solid-state batteries 100, 100a with an SEM, measuring the thickness at ten different points in one layer, and deriving the average value.

[0054] Next, a description will be given of a method for manufacturing the all-solid-state battery 100a illustrated in Fig. 3. Fig. 6 is a diagram illustrating a flow of the method for manufacturing the all-solid-state battery 100a.

[0055] (Process for producing raw powder for solid electrolyte layer) First, a raw material powder for the solid electrolyte layer constituting the above-mentioned solid electrolyte layer 30 is prepared. For example, raw materials, additives, etc. are mixed, and a solid-phase synthesis method or the like is used to prepare raw material powder for an oxide-based solid electrolyte. The obtained raw material powder can be dry-milled to adjust to a desired average particle size. For example, a planetary ball mill using 5 mmφ ZrO2 balls is used to adjust to a desired average particle size.

[0056] (Cover layer raw powder preparation process) First, the raw material powder of the ceramics constituting the above-mentioned cover layer 50 is prepared. For example, the raw material powder for the cover layer can be prepared by mixing the raw materials, additives, etc., and using a solid-phase synthesis method, etc. The obtained raw material powder can be adjusted to a desired average particle size by dry pulverizing. For example, the desired average particle size is adjusted using a planetary ball mill using 5 mmφ ZrO2 balls.

[0057] (Internal electrode paste manufacturing process) Next, the internal electrode pastes for producing the above-mentioned positive electrode layer 10 and negative electrode layer 20 are separately prepared. For example, the electrode active material and the solid electrolyte material are highly dispersed using a bead mill or the like to produce a ceramic paste consisting only of ceramic particles. The conductive assistants 13 and 23 are mixed into this ceramic paste. When fibrous carbon is used as the conductive assistants 13 and 23, a dispersion process is performed using a solvent for the paste and an appropriate dispersant using an ultrasonic homogenizer or a wet jet mill. The ceramic paste, the dispersion of the conductive assistants 13 and 23, and the binder are mixed to produce the electrode layer paste.

[0058] The sintering aid of the internal electrode paste contains one or more glass components such as Li-BO based compounds, Li-Si-O based compounds, Li-CO based compounds, Li-SO based compounds, and Li-PO based compounds.

[0059] (External electrode paste manufacturing process) Next, an external electrode paste for producing the above-mentioned first external electrode 40a and second external electrode 40b is prepared. For example, the external electrode paste can be obtained by uniformly dispersing a conductive material, a glass frit, a binder, a plasticizer, etc. in water or an organic solvent.

[0060] (Solid electrolyte green sheet manufacturing process) The raw material powder for the solid electrolyte layer is uniformly dispersed in an aqueous or organic solvent together with a binder, a dispersant, a plasticizer, etc., and wet-pulverized to obtain a solid electrolyte slurry having a desired average particle size. At this time, a bead mill, a wet jet mill, various kneaders, a high-pressure homogenizer, etc. can be used, and it is preferable to use a bead mill from the viewpoint of simultaneously adjusting the particle size distribution and dispersing. A binder is added to the obtained solid electrolyte slurry to obtain a solid electrolyte paste. The obtained solid electrolyte paste is coated to produce a solid electrolyte green sheet 51. The coating method is not particularly limited, and a slot die method, a reverse coat method, a gravure coat method, a bar coat method, a doctor blade method, etc. can be used. The particle size distribution after wet-pulverization can be measured, for example, using a laser diffraction measurement device using a laser diffraction scattering method.

[0061] (Lamination process) As illustrated in FIG. 7(a), the internal electrode paste 52 is printed on one side of the solid electrolyte green sheet 51. In the area on the solid electrolyte green sheet 51 where the internal electrode paste 52 is not printed, the reverse pattern 53 is printed. The reverse pattern 53 can be the same as the solid electrolyte green sheet 51. A plurality of printed solid electrolyte green sheets 51 are alternately shifted and stacked. As illustrated in FIG. 7(b), a laminate is obtained by pressing the cover sheets 54 from above and below in the stacking direction. In this case, a laminate having a substantially rectangular parallelepiped shape is obtained so that the internal electrode paste 52 for the positive electrode layer 10 is exposed on one end surface of the laminate and the internal electrode paste 52 for the negative electrode layer 20 is exposed on the other end surface of the laminate. The cover sheet 54 can be formed by applying the raw material powder for the cover layer in the same manner as in the solid electrolyte green sheet preparation process. The cover sheet 54 is formed to be thicker than the solid electrolyte green sheet 51. It may be made thicker during coating, or it may be made thicker by stacking multiple coated sheets.

[0062] Next, the external electrode paste 55 is applied to each of the two end faces by a dipping method or the like, and then dried, thereby obtaining a molded body for forming the all-solid-state battery 100a.

[0063] (Firing process) Next, the obtained laminate is fired. The firing conditions are not particularly limited, and may be in an oxidizing or non-oxidizing atmosphere, and the maximum temperature is preferably 400°C to 1000°C, more preferably 500°C to 900°C, etc. In order to sufficiently remove the binder before the maximum temperature is reached, a step of maintaining the temperature in an oxidizing atmosphere at a temperature lower than the maximum temperature may be provided. In order to reduce process costs, it is desirable to fire at as low a temperature as possible. After firing, a reoxidation treatment may be performed. Through the above steps, an all-solid-state battery 100a is produced.

[0064] In addition, a collector layer can be formed in the positive electrode layer 10 and the negative electrode layer 20 by sequentially laminating an internal electrode paste, a collector paste containing a conductive material, and an internal electrode paste. EXAMPLES

[0065] Example 1 The electrode active material and the solid electrolyte were highly dispersed in a bead mill to prepare a ceramic paste consisting of only ceramic particles. Multi-layered carbon nanotubes were used as the conductive assistant. Since the multi-layered carbon nanotubes are entangled, they were dispersed using a solvent for the paste and an appropriate dispersant by an ultrasonic homogenizer or a wet jet mill. The conditions of the dispersion treatment were adjusted so that the aspect ratio of the fiber diameter of the carbon nanotubes was 100:1 to 1000:1. The ceramic paste, the dispersion liquid of the carbon nanotubes, and the binder were mixed to prepare an electrode paste. Then, the electrode paste was printed and laminated on the solid electrolyte green sheet, and fired to form an external electrode to prepare an all-solid-state battery. In Example 1, carbon nanotubes with a GD ratio of 1.9 were used. The GD ratio was measured using a Raman spectrometer (NRS-3300 manufactured by JASCO Corporation).

[0066] The cross section of the sintered battery was polished by ion milling and observed with a SEM to determine the average diameter and area ratio of each carbon nanotube contained in the electrode layer. In each electrode layer after firing, the average diameter of the carbon nanotubes was 15 nm, and the area ratio of the carbon nanotubes was 1%. In addition, the thickness of the solid electrolyte layer after firing was 20 μm.

[0067] Example 2 In Example 2, carbon nanotubes with a GD ratio of 4 were used. In each electrode layer after firing, the average diameter of the carbon nanotubes was 70 nm, and the area ratio was 1%. In addition, the thickness of the solid electrolyte layer after firing was 20 μm.

[0068] Example 3 In Example 3, carbon nanotubes with a GD ratio of 4 were used. In each electrode layer after firing, the average diameter of the carbon nanotubes was 70 nm and the area ratio was 4%. In addition, the thickness of the solid electrolyte layer after firing was 20 μm.

[0069] Example 4 In Example 4, carbon nanotubes with a GD ratio of 4 were used. In each electrode layer after firing, the average diameter of the carbon nanotubes was 70 nm and the area ratio was 4%. In addition, the thickness of the solid electrolyte layer after firing was 10 μm.

[0070] Example 5 In Example 5, carbon nanotubes with a GD ratio of 15 were used. In each electrode layer after firing, the average diameter of the carbon nanotubes was 130 nm, and the area ratio was 4%. In addition, the thickness of the solid electrolyte layer after firing was 20 μm.

[0071] Comparative Example 1 In Comparative Example 1, carbon nanotubes with a GD ratio of 4 were used. In each electrode layer after firing, the average diameter of the carbon nanotubes was 70 nm and the area ratio was 0.5%. In addition, the thickness of the solid electrolyte layer after firing was 20 μm.

[0072] Comparative Example 2 In Comparative Example 2, carbon nanotubes with a GD ratio of 15 were used. In each electrode layer after firing, the average diameter of the carbon nanotubes was 130 nm, and the area ratio was 4%. In addition, the thickness of the solid electrolyte layer after firing was 4 μm.

[0073] Comparative Example 3 In Comparative Example 3, carbon nanotubes with a GD ratio of 15 were used. In each electrode layer after firing, the average diameter of the carbon nanotubes was 150 nm and the area ratio was 4%. In addition, the thickness of the solid electrolyte layer after firing was 20 μm.

[0074] Comparative Example 4 In Comparative Example 4, carbon nanotubes with a GD ratio of 4 were used. In each electrode layer after firing, the average diameter of the carbon nanotubes was 70 nm and the area ratio was 4%. In addition, the thickness of the solid electrolyte layer after firing was 25 μm.

[0075] (Evaluation of electrode resistance) The electrode resistance was measured for each of Examples 1 to 5 and Comparative Examples 1 to 4. The electrode resistance was measured by preparing a sintered body consisting of only the electrode and using a DC resistance meter. If the electrode resistance was 2 Ω·cm or less, the electrode resistance was judged as pass (good). If the electrode resistance was more than 2 Ω·cm, the electrode resistance was judged as fail (bad).

[0076] (Rate characteristic evaluation) The rate characteristics were evaluated for each of Examples 1 to 5 and Comparative Examples 1 to 4. The rate characteristics were evaluated by performing CC charge / discharge measurements at 25° C. (charge / discharge current 0.2C or 1.0C, upper cutoff voltage 3.3V, lower cutoff voltage 2.0V) to determine the ratio of the 1C discharge capacity to the 0.2C discharge capacity of 100%, and if the ratio was 70% or more, the rate characteristics were judged as passing "◯". If the ratio was less than 70%, the rate characteristics were judged as failing "X".

[0077] (Battery capacity evaluation) The battery capacity was evaluated for each of Examples 1 to 5 and Comparative Examples 1 to 4. The battery capacity was determined by the capacity of 0.2 C discharge during the rate characteristic measurement. The ratio of the discharge capacity value under each condition to the battery capacity of Example 3 taken as 100% was calculated, and if the ratio was 90% or more, the battery capacity was judged as pass "◯". If the ratio was less than 90%, the battery capacity was judged as fail "X".

[0078] (Short circuit rate evaluation) The short circuit rate was evaluated for each of Examples 1 to 5 and Comparative Examples 1 to 4. The short circuit rate was measured by the number of short circuits that occurred among 50 samples. If the short circuit rate was 5% or less, the short circuit rate was judged as a pass mark "◯". If the short circuit rate was more than 5%, the short circuit rate was judged as a fail mark "X".

[0079] (Overall Judgment) If the electrode resistance, rate characteristics, capacity, and short rate were all judged as passing "O", the overall judgment was judged as passing "O". If any one of the electrode resistance, rate characteristics, capacity, and short rate was judged as failing "X", the overall judgment was judged as failing "X". The results are shown in Table 1. [Table 1]

[0080] The overall evaluation was "good" for all of Examples 1 to 5. This is believed to be because the GD ratio of the conductive assistant was 0.5 or more and 20 or less, the average diameter of the conductive assistant in the cross section of the electrode layer was 5 nm or more and less than 150 nm, the area ratio of the conductive assistant in the cross section of the electrode layer was more than 0.5% and 10% or less, and the thickness of the solid electrolyte layer was 5 μm or more and 20 μm or less.

[0081] In Comparative Example 1, the area ratio of the conductive assistant is low, which is believed to have increased the electrode resistance and deteriorated the rate characteristics and battery capacity. In Comparative Example 2, the short circuit rate is believed to have increased because the solid electrolyte layer is thin. In Comparative Example 3, the short circuit rate is believed to have increased because the average diameter of the conductive assistant is large. In Comparative Example 4, the rate characteristics are believed to have deteriorated because the solid electrolyte layer is thick.

[0082] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to such specific embodiments, and various modifications and variations are possible within the scope of the gist of the present invention described in the claims. [Explanation of symbols]

[0083] 10 Positive electrode layer 11 Electrode active material 12 Solid electrolyte 13 Conductive additives 15 First current collector layer 20 Negative electrode layer 21 Electrode active material 22 Solid electrolyte 23 Conductive additives 25 Second collector layer 30 Solid electrolyte layer 40a First external electrode 40b 2nd external electrode 50 Cover Layer 51 Solid electrolyte green sheet 52 Internal electrode paste 53 Reverse pattern 54 Cover Sheet 55 External electrode paste 60 Stacked Chips 70 side margin 100,100a solid state battery

Claims

1. A solid electrolyte layer; an electrode layer provided on each of the main surfaces of the solid electrolyte layer and including an electrode active material and a carbon-based conductive assistant; In a cross section of each of the electrode layers, the average diameter of the conductive assistant is 5 nm or more and less than 150 nm, and the GD ratio of the conductive assistant is 0.5 or more and 20 or less, In a cross section of the electrode layer, an area ratio of the conductive assistant is more than 0.5% and 10% or less; The solid electrolyte layer has a thickness of 5 μm or more and 20 μm or less.

2. The all-solid-state battery according to claim 1 , wherein the conductive assistant is a fibrous conductive material.

3. The all-solid-state battery according to claim 1 , wherein the conductive assistant is a carbon nanotube.

4. The all-solid-state battery according to claim 1 , wherein the conductive assistant is a multi-walled carbon nanotube.

5. The all-solid-state battery according to claim 1 , wherein the solid electrolyte layer is an oxide.

6. The all-solid-state battery according to claim 1 , wherein the solid electrolyte layer is a phosphate-based oxide.

7. The all-solid-state battery according to claim 1 , wherein the solid electrolyte layer and the electrode layer are sintered bodies.

Citation Information

Patent Citations

  • All-solid-state battery, green laminate for all-solid-state battery, and method for producing all-solid-state battery

    WO2014042083A1

  • Solid electrolyte layer, and all-solid battery using said solid electrolyte layer

    WO2021095757A1